Clinical and Microbiological Significance of the Specificity, Composition and Functional Differences of Dysbiosis in Children and Adults - Nuruzova, Z. A. (American Journal of Bioscience and Clinical Integrity, 2024)
The gut microbiota has a significant impact on the development, maturation and differentiation of the immune system. It has a significant impact on the mental and physical development of the child. Large-scale cohort studies can provide a more complete picture of the differences between people and more accurately characterize how the gut microbiota affects human physiology and disease processes. The formation of the intestinal microbiota begins in utero or immediately after birth, and by the age of three its composition completely changes and becomes the same as in adults. In childhood, it is very important to form a balanced gut microbiota, because dysbiosis can continue into adulthood. The human intestinal microbiota may play a fundamental role in the risk of developing diseases that can be programmed at an early age, and studies have shown that dysbiosis, or imbalance of the intestinal microbiota at an early age, is associated with specific disease outcomes in children or adults, including obesity, cardiovascular diseases, neurological disorders. disorders, atopic dermatitis, diabetes, asthma and other allergic diseases. In fact, it is extremely important to investigate the role of the human gut microbiota at an early age. Thus, research is currently focused on factors affecting the gut microbiota of infants. This review discusses the latest results of our research on how various factors, such as the type of delivery, type of diet and medication, including antibiotics, affect the intestinal microflora of infants. It also discusses promising methods for preventing and restoring dysbiosis in children and adults.